Development of a wireless charging system for electric vehicles - Cai, Jing Xian (2017)
Wireless charging technology has a broad market prospects because of its convenience and reliability. The purpose of this project is to design and implement a wireless charging system that can charge for mobile phones. The ultimate goal of the project is to explore new charging technology in order to achieve wireless charging for different types of electronic equipment and electric vehicles. Thus wireless charging technology can be more widely applied. The project consists of different types of circuit modules, including the transmitting module, the receiving module and the USB charging module. The project uses a resonant charging method in which the frequency between the transmitter and the receiver module is 180 kHz. Wireless chargers can improve efficiency by changing the coil type and number of turns. The project eventually designs a wireless charger capable of measuring the receiver voltage and charging the mobile phones.